Antihyperlipidemic and antioxidant effects of feather protein hydrolysate in high‐fat diet‐fed mice. Issue 3 (10th February 2019) - Ben Hamad Bouhamed, Sana; Chaari, Marwa; Bellassoued, Khaled; Naifar, Manel; Makni‐Ayadi, Fatma; Boudaouara, Tahia; El Feki, Abdelfattah; Kechaou, Nabil
Abstract: The hyperlipidemia is a serious health problem that increases the risk of many complications including cardiovascular disease. This study aims to evaluate the possible antihyperlipidemic effects of the feather protein hydrolysate (FPH) in a mice fed with a high‐fat diet (HFD)‐fed mice during 5 weeks. The FPH administration improved dose‐dependent lipid profile, as well as the liver and renal dysfunction indices in hyperlipidemic mice. The FPH also restored the antioxidant status in liver, kidney, and heart by lowering the lipid peroxidation and enhancing the antioxidant enzymes (catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase [SOD]). Moreover, the histological studies proved that FPH administration prevents hepatic steatosis, glomerular hyperfiltration risk, and cardiac muscle hypertrophy. Accordingly, the FPH is a promising novel medicinal ingredient for possible use in the hyperlipidemic treatment and related complications.